PEMBINAAN MANAJEMEN PELAKSANAAN KEGIATAN QURBAN DALAM PERSPEKTIF SYARIAT ISLAM PADA JAMAAH MASJID AL JIHADURROHMAN PUDAK PAYUNG BANYUMANIK SEMARANG TAHUN 2024 - Abidin, Zaenal; Isnaini, Isnaini (Tahta Media Grup, 2024)
The aim of this community service activity is to educate administrators about managing the implementation of sacrificial activities during Eid al-Adha based on Islamic law. It is also hoped that we can find out the efforts and results made by the committee and mosque congregation in overcoming obstacles to empowerment in managing the implementation of qurban activities during Eid al-Adha which are based on Islamic law at the Al Jihadurrohman Mosque Pudak Payung Banyumanik Semarang. This service was carried out at the Al Jihadurrohman Mosque Pudak Payung Banyumanik Semarang. Coaching participants in this service. consisting of: Takmir, Committee, and congregation of the Al Jihadurrohman Mosque Pudak Payung Banyumanik Semarang. This service uses lecture methods and questions and answers in a discussion forum at the Al Jihadurrohman Mosque Pudak Payung Banyumanik Semarang. Management of the implementation of sacrificial activities during Eid al-Adha based on Islamic law is one of the important things to convey to ordinary people in the post-pandemic era. The obstacle that occurred during the training was that there were several congregants who were not familiar with Islamic Sharia law.